Mapping of Landslide Susceptibility based on Analytical Hierarchy Process (AHP) in Sermo Dam and its Surrounding Areas, Kokap, Kulon Progo - Rizqi, Al hussein Flowers; Sidik, Vilman; Fatimah, Fatimah; Kusuma Wijayanti, Herning Dyah; Fatih Qodri, Muhammad (ReTII, 2021)
The Nanggulan Formation as the oldest formation in the Kulon Progo Mountains is not only exposed in a type location in the Nanggulan area, Kalibawang. However, in the western area of ​​the Sermo Reservoir, precisely in the hills around the Kokap, the Nanggulan Formation is found in several places. The existence of the Nanggulan Formation around the Sermo Reservoir is suspected to have triggered the occurrence of ground movements in this area. The purpose of this research is to map the ground motion. The purpose of the study was to determine the potential for ground motion in the study area. The research area is included in the southern Kulon Progo Dome Mountain Zone. This ground motion zoning mapping was carried out based on the AHP (methodAnalytical Hierarchy Process) using the weighted values ​​of four parameters. The parameters used are slope, lithology, land use and rainfall. The results of AHP processing using Arc GIS software produce a landslide susceptibility zoning map which is divided into 5 classes (very low, low, medium, high and very high). Based on the results of mapping using the AHP method, the most vulnerable area is Hargowilis Village which is composed of claystone lithology from the Nanggulan Formation. Keywords: Landslides, Nanggulan, Sermo, AHP, Kulon Progo